The Budget-Limit Effect on the Delegation of the Capital Budgeting Authority: The Case of Sequential and Frequent Investment Decisions - Sharon, Ed M. (Management Science, 1983)
Publishing houses, Savings & Loans and other business firms make frequent long-term investment decisions, and in sequence. Typically they encounter more short-lived investment opportunities than their budget can accommodate. Some will even go out of their way to broaden their horizon of choices. As a result, one will find some organizations which satisfy their needs by choosing opportunities from a relatively narrow horizon, and others which are engaged in an extensive evaluation process whose objective is to gradually narrow down the options available. The latter effort typically covers various layers in the organizations, both at the division (branch) and headquarters (HQ). Common sense may suggest that the more limited capital resources are, the larger should be the set of explored opportunities, and the more careful (centralized) should the decision making process be. A quantitative approach to the problem is presented here, which captures the relationships between investment-opportunities-horizon “size” and “quality,” the value of funds to be invested, the cost of narrowing the options down, and the limits to centralization/decentralization, all under a limited budget. It demonstrates that under certain conditions the intuitively optimal mode of centralization becomes less than optimal, and decentralization is the rational and consistent mode. Other difficult questions such as “how broad is a broad enough horizon of choices?” are addressed.